2022
DOI: 10.3390/jcm11092398
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Plasminogen Activator as a Possible Indicator of Breast Cancer Relapse: A Preliminary, Prospective Study

Abstract: (1) Background: The fundamental causes of breast cancer mortality are the cancer spread and hypercoagulability state. The study aimed to evaluate the prognostic efficacy of the fibrinolytic profile concerning 5-year follow-up. (2) Methods: We investigated the predictive potential of the plasma activity of urokinase plasminogen activator (u-PA) and plasminogen activator inhibitor type 1 (PAI-1) as well as antigen of tissue plasminogen activator (t-PA), u-PA, PAI-1, and PAI-1/t-PA and PAI-1/u-PA complexes in 41 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Cancer treatment includes surgery, chemotherapy, radiotherapy, hormone therapy, and immunotherapy. BC treatment is more difficult after metastasis and recurrence [ 2 ]. Relapses are linked to multi-drug resistance (MDR) characteristics such as increased efflux transporter expression and activation of transcription factor genes that lead to mutations and proliferation of cancer cells [ 3 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer treatment includes surgery, chemotherapy, radiotherapy, hormone therapy, and immunotherapy. BC treatment is more difficult after metastasis and recurrence [ 2 ]. Relapses are linked to multi-drug resistance (MDR) characteristics such as increased efflux transporter expression and activation of transcription factor genes that lead to mutations and proliferation of cancer cells [ 3 ].…”
mentioning
confidence: 99%
“…Tissue plasminogen activator (t-PA) antigen and plasminogen activator inhibitor-1 (PAI-1) have been recently described as biomarkers with high prognostic potential. A clinical study demonstrated that low plasma concentrations of t-PA antigen and higher PAI-1 activity are shown to be strong predictors for distant metastasis and independent prognostic markers in BC patients [ 2 ].…”
mentioning
confidence: 99%
“…Winther-Larsen et al (18) systematically evaluated hyperfibrinolysis in 21 patients with malignant solid tumors, with prostate cancer (76%) being the most common type, while there have been few reports of hyperfibrinolysis in patients with breast cancer (17,21). Breast cancer cells contain abundant plasminogen activators (t-PA and u-PA), and with the progression of tumors, plasminogen activator in tumor cells is released into the blood in large amounts, causing enhanced fibrinolytic system function (22)(23)(24). ii) The tumor cell membrane also carries a specific u-PA-receptor (u-PAR), which contributes to the assembly of fibrinolytic components and promotes the activation of the fibrinolytic cascade (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer cells contain abundant plasminogen activators (t-PA and u-PA), and with the progression of tumors, plasminogen activator in tumor cells is released into the blood in large amounts, causing enhanced fibrinolytic system function (22)(23)(24). ii) The tumor cell membrane also carries a specific u-PA-receptor (u-PAR), which contributes to the assembly of fibrinolytic components and promotes the activation of the fibrinolytic cascade (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated associations between cancer progression and serum levels of tPA (not in tumours). For example, low plasma/serum level of tPA was associated with poor disease‐free survival and enhanced risk of breast cancer progression [ 61 ]. While, in other studies, higher levels of plasma tPA are linked to a greater risk of breast cancer and aggressive disease [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%